Process modeling of recombinant adeno-associated virus production in HEK293 cells. (June 2022) - Joiner, Jordan; Huang, Zhuangrong; McHugh, Kyle; Stebbins, Matthew; Aron, Kathryn; Borys, Michael; Khetan, Anurag
Abstract : With a high required dosing and relatively low process efficiency, providing recombinant adeno-associated virus (rAAV) supply for clinical trials and commercial demand remains challenging. One of the most widely used protocols to produce rAAVs is transient transfection of HEK293 cells. Despite decades of research, there are relatively few studies that focus on key factors in rAAV manufacturing processes. Only about 5–30% of rAAV capsids produced by cells contain the therapeutic element, causing low yields and an immense burden on downstream purification. Modeling approaches are valuable tools for bioprocess understanding and optimization. This review summarizes the recent mechanistic models of HEK293 metabolism and rAAV production. We also provide an outline for future development of hybrid mechanistic and data-driven models for understanding the underlying mechanisms and identifying critically relevant process variables.